Re-examining the Relationship between Domestic Investment and Foreign Aid : Does Political Stability Matter? - Dutta, Nabamita; Mukherjee, Deepraj; Roy, Sanjukta (Taylor and Francis, 2015)
While past studies had conflicting conclusions regarding the impact of foreign aid on growth and development of a nation, recent studies have tried to delve deeper into the question, ‘what makes aid work?’ (see, Dutta, Leeson, and Williamson, 2013; Burnside and Dollar, 2000, 2004; Svensson, 1999). This paper tests how political stability (vis-à-vis political instability) affects the relationship between domestic investment and foreign aid. Applying dynamic panel estimators, our results show that political stability affects aid’s effectiveness on domestic capital formation. The paper considers alternative measures of political stability (vis-à-vis instability), focusing on the political characteristics of a system that have the potential to make a nation stable. Political stability affects policy selection by the government positively and, thus, public resources such as foreign aid are put to the desired use. The estimated marginal impacts show that foreign aid enhances domestic investment in the presence of a stable political climate, but there is a diminishing return to aid.